Osteogenic differentiation of human gingival mesenchymal stem cells by Aristolochia bracteolata supplementation through enhanced Runx2 expression. Issue 7 (21st February 2017) - Murugan Girija, Dinesh; Y Ranga Rao, Suresh; Kalachaveedu, Mangathayaru; Subbarayan, Rajasekaran
Abstract : The phenotypic characteristics of human gingival derived mesenchymal stem cells (HGMSCs) on induction with total methanol extract of Aristolochia bracteolata have been evaluated. HGMSCs were cultured in control and two different induction medium: Control medium (basal medium), OM1 (Standard induction medium), and OM2 (100 μg/ml of A. bracteolata ). Osteogenic differentiation of the cultured cells was assessed by studying the calcium deposition and osteoblastic gene expression. OM2 medium showed an enhanced osteogenic differentiation potential than OM1 as measured by increased calcium deposition and elevated expression of Runx2, osteopontin, osteonectin, osteocalcin, Collagen type I, and ALP levels in comparison with OM1 differentiated cells. We conclude that at 100 μg/ml A. bracteolata has induced HGMSC differentiation into osteogenic lineage consequent to enhanced Runx2 expression and related osteogenic genes. Abstract : The phenotypic characteristics of human gingival derived mesenchymal stem cells (HGMSCs) on induction with total methanol extract of Aristolochia bracteolata have been evaluated. A. bracteolata has induced HGMSC differentiation into osteogenic lineage consequent to enhanced Runx2 expression and related osteogenic genes.